Feasibility study for clinical application of caspase‐3 inhibitors in Pemphigus vulgaris. Issue 12 (27th December 2017) - Hariton, William V.J.; Galichet, Arnaud; Vanden Berghe, Tom; Overmiller, Andrew M.; Mahoney, My G.; Declercq, Wim; Müller, Eliane J.
Abstract: The potentially severe side effects of systemic corticosteroids and immunosuppressants used in Pemphigus vulgaris (PV) call for novel therapeutic approaches. In this context, pharmacological inhibition of major pathogenic signalling effectors represents a promising alternative. However, we have also shown that overinhibition of effectors required for epidermal homeostasis can exacerbate PV pathophysiology implicating transepidermal keratinocyte fragility. A feedforward target validation therefore preferentially includes studies on knockout mouse models. We previously reported on successful amelioration of PV blisters following inhibition of non‐apoptotic, low‐level caspase‐3. Here, we use conditional, keratinocyte‐specific caspase‐3‐deficient mice (casp3 EKO ) to demonstrate (i) absence of keratinocyte fragility upon injection of the potent Dsg3‐specific antibody AK23 and (ii) amelioration of blistering on the background of known signalling effectors. Our results provide the experimental proof of concept justifying translation of the caspase‐3 inhibitor approach into PV clinical trials.